Keakuratan Kode Diagnosis Penyakit Berdasarkan ICD-10 pada Rekam Medis Rawat Jalan Di Puskesmas - Irmawati Irmawati; Nadelia Nazillahtunnisa (Poltekkes Kemenkes Semarang, 2019)
An accurate diagnostic code is required to achieve the goal of the classification system for disease diagnosis, one of which is the recording of mortality and morbidity data. Based on preliminary study of 7 samples of medical records in health centers Kagok, get results 2 medical records (28.57%) there is an accurate diagnosis and diagnostic code and 4 medical records (57.14%) there is an inaccurate diagnosis and diagnosis code, while 1 medical record (14.29%) no diagnosis. The purpose of this research is to determine the accuracy of the disease diagnosis code based on ICD-10 in the outpatient medical record in health centers Kagok. This study used a quantitative descriptive research with cross sectional research design. The number of samples on this study was 98 medical records of outpatient patients, taken with a proportional stratified sampling method. The results showed that the medical record was diagnosed as much as 57 medical records (58%) while the unwritten diagnosis is as much as 41 medical record (42%). From 57 medical records that have been diagnosed, there are only 18 medical records (32%) with accurate code and 39 medical records (68%) with inaccurate code. The officers of the Diagnosis Code no one has the educational background of the medical record, never participated in special training on coding ICD-10, and did not use the facilities in the health centers in the form of an electronic ICD-10 in giving code diagnosis.